An Analysis of Idiom on the Bridge to Terabithia Movie - Hoar, Jeni Yulfrida; Siahaan, Desta Gloria (UICELL, 2023)
The aim of this study was to find types and analyze meaning of idiom on the Bridge to Terabithia Movie. To analyze the data, the researchers used qualitative method. In addition, the researchers used data documentary to collect the data, because the data were taken from the dialogues of the Movie. The idioms in the movie were examined using Christopher's theory. Types of idioms used in the movie are prepositional Idiom, Pure Idiom and Partial Idiom Based on Christopher theory of idiom. Not all of the types of idioms used in this movie. There are Binomial idiom, Proverbs, Euphemism and Cliché. There are 34 cases of idiom found in Bridge to Terabithia Movie. There are 17 (56, 7 %) case of Prepositional Idiom, 12 (40 %) case of Pure Idiom and one case of Partial Idiom (3,3 %). The most dominant type of idiom in Bridge to Terabithia movie is Prepositional Idiom, which represent 17 cases with percentage 56, 7 %. This implication of this research is to enrich the vocabulary especially about idioms for readers especially student. Keywords: Idiom, Bridge to Terabithia Movie, qualitative method